Characterisation of irradiation-induced defects in ZnO single crystals. (January 2016) - Prochazka, I; Cizek, J; Lukac, F; Melikhova, O; Valenta, J; Havranek, V; Anwand, W; Skuratov, V A; Strukova, T S
Abstract: Positron annihilation spectroscopy (PAS) combined with optical methods was employed for characterisation of defects in the hydrothermally grown ZnO single crystals irradiated by 167 MeV Xe 26+ ions to fluences ranged from 3×10 12 to 1×10 14 cm -2 . The positron lifetime (LT), Doppler broadening as well as slow-positron implantation spectroscopy (SPIS) techniques were involved. The ab-initio theoretical calculations were utilised for interpretation of LT results. The optical transmission and photoluminescence measurements were conducted, too. The virgin ZnO crystal exhibited a single component LT spectrum with a lifetime of 182 ps which is attributed to saturated positron trapping in Zn vacancies associated with hydrogen atoms unintentionally introduced into the crystal during the crystal growth. The Xe ion irradiated ZnO crystals have shown an additional component with a longer lifetime of ≈ 360 ps which comes from irradiation-induced larger defects equivalent in size to clusters of ≈10 to 12 vacancies. The concentrations of these clusters were estimated on the basis of combined LT and SPIS data. The PAS data were correlated with irradiation induced changes seen in the optical spectroscopy experiments.